2022
DOI: 10.3390/jcm11102751
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccination Rate and SARS-CoV-2 Infection of Health Care Workers in Aerosol-Generating Medical Disciplines

Abstract: Healthcare workers (HCW) who perform aerosol-generating procedures (AGP) are at high risk of SARS-CoV-2 infection. Data on infection rates and vaccination are limited. A nationwide, cross-sectional study focusing on AGP-related specialties was conducted between 3 May 2021 and 14 June 2021. Vaccination rates among HCW, perception of infection risk, and infection rates were analyzed, focusing on the comparison of gastrointestinal endoscopy (GIE) and other AGP-related specialties (NON-GIE), from the beginning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Further, most of the survey respondents in both the 2020/21 group and the 2022 Omicron group indicated that they felt safe with the PPE they were provided. This contrasts with the results of the previous studies reporting low HCW satisfaction with PPE provided and safety at work [15][16][17][18][19] . In a study that was conducted in Qatar from June 2020 to July 2020, Ismail et.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Further, most of the survey respondents in both the 2020/21 group and the 2022 Omicron group indicated that they felt safe with the PPE they were provided. This contrasts with the results of the previous studies reporting low HCW satisfaction with PPE provided and safety at work [15][16][17][18][19] . In a study that was conducted in Qatar from June 2020 to July 2020, Ismail et.…”
Section: Discussioncontrasting
confidence: 99%
“…al conducted in Singapore from July 2020 to September 2020 also found that only 13.7% of the participating HCW were 'highly confident' of the protection provided by the PPE 17 . However, the measures used to evaluate "feeling safe" or "satisfaction with" or "being confident" with the PPE used in these studies were different, and it is also important to keep in mind that these studies took place in different countries during a different time period when PPE shortage could have been possibly a more pertinent issue [15][16][17][18][19] . Interestingly, in our HCW survey we found a significant difference between nurses and physicians in terms of how safe they felt with the PPE they were provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our findings, the rate of resident doctors who adhered to the COVID-19 vaccination programme is close to 100%; in fact, only 0.26% of them did not receive a vaccination. These results show a very high compliance rate of MRs towards compulsory vaccination even compared to studies performed in other states [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 48%